Student attainment measurement system in civil engineering undergraduate programme: a satisfaction survey / Mazlina Mohamad …[et al.] - Mohamad, Mazlina; Lian, Oh Chai; Md Zain, Mohd Raizamzamani; Md Yunus, Balqis; Sidek, Norbaya (Universiti Teknologi MARA, 2021)
In ensuring the quality of the offered programs in Malaysia, it is crucial to comply with the long chain of Quality Management processes in obtaining and maintaining accreditation of undergraduate engineering programs. One of the processes is to continually and effectively measure the students’ attainment of program outcomes amid the implementation of Outcome-Based Education. This paper focuses on MyCOPO system, the evaluation of undergraduate bachelor degree engineering students’ attainment measurement system in the Faculty of Civil Engineering, Universiti Teknologi MARA, Shah Alam. A quantitative survey has been conducted to measure academic staff and students’ satisfaction level of MyCOPO implementation in the faculty. This survey has been conducted in line with the university strategy in promoting organisation operational excellence via MyCOPO system, where 47 and 227 respondents were recorded for academic staff and students, respectively. Two sets of questionnaires were designed to determine the impact of the system, the effectiveness on delivery and quality of the system and users’ happiness index. This system is found to be impactful in ease the work, increase the quality and provide satisfaction to related parties. The usage of MyCOPO system is effective and the average rating of happiness index for academic staff and students are 8.2 and 7.2 out of 10 for happiness index, respectively.